Arabic Prepositions used as Nouns, Verbs or Both: حروف الجر المشتركة (ما استعمل منها: اسمًا، أو فعلاً، أو كليهما) (المجلة العربية للعلوم و نشر الأبحاث, 2018)
Al harf (particle) is an important element in Arabic as it carries a lot of meanings. So, a good number of researches have been done on these particles either as part of a book such as Sibawayh in the al Kitab and Ibn Siraj in al Osool or in separate whole books such as Huruf al- Ma'ani for Zajjaji and al Jana al- Dani fi Huruf al- Ma’ani for Muradi. The grammarians have divided particles into three categories among which Huruf al Ma’ani which are used for nouns and verbs. This important category, including conjunctions, Negation particles, prepositions, etc., received a lot of attention by grammarians and researchers. This study investigates the ways in which Arabic prepositions are used as nouns, verbs or both. The research consists of, apart from abstract and introduction, three parts: prepositions used as nouns or verbs such as ala and hasha; prepositions used as verbs such as ada and khala ; prepositions used as nouns such as al kaf, an, munthu, muth, ma’a and mata. The study concludes by summarizing the main findings of the study.